Effect of Surfactant on Growth of ZnO Nanodumbbells and Their Characterization - Sunil Babu Eadi; Sungjin Kim; Soon Wook Jeong (Journal of Chemistry)
We report the controlled synthesis of dumbbell shaped ZnO micro/nanostructures using anionic surfactant sodium dodecyl sulphate (SDS) by simple one-step hydrothermal method. The morphology changes of ZnO were characterized by using scanning electron microscopy, X-ray diffraction, and energy dispersive spectroscopy. It is found that the size of the dumbbell increased with increase in concentration of SDS. Systematic growth mechanism with increase of concentration of SDS polymer is studied. Our results will help in the growing face selective ZnO for many functional applications.